2008
DOI: 10.1121/1.2832329
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency wind noise contributions in measurement microphones

Abstract: In a previous paper [R. Raspet, et al., J. Acoust. Soc. Am. 119, 834-843 (2006)], a method was introduced to predict upper and lower bounds for wind noise measured in spherical wind-screens from the measured incident velocity spectra. That paper was restricted in that the predictions were only valid within the inertial range of the incident turbulence, and the data were from a measurement not specifically designed to test the predictions. This paper extends the previous predictions into the source region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 12 publications
3
31
1
Order By: Relevance
“…Raspet et al 1 developed theories relating the wind noise measured by screened and unscreened microphones to meteorological measurements at the height of the microphone. Reference 1 also established fitting and analysis procedures for the turbulence spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Raspet et al 1 developed theories relating the wind noise measured by screened and unscreened microphones to meteorological measurements at the height of the microphone. Reference 1 also established fitting and analysis procedures for the turbulence spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the reduction due to anisotropy, the cross flow term is larger than the intrinsic turbulence-turbulence interaction and the mean shearturbulence interaction discussed in Ref. 8. The cross flow terms should be the dominant contribution for our measurement in the surface layer for wave number k Ͼ 0.01 m −1 .…”
Section: Theorymentioning
confidence: 94%
“…In a previous paper, Raspet et al 8 showed that the stagnation pressure calculated from measurements of the average wind speed and measured turbulence spectra provides a good estimate of the wind noise measured by a gridded bare microphone in a turbulent outdoor flow near the ground. The stagnation pressure is given by…”
Section: Theorymentioning
confidence: 99%
“…2 of Fee and Garcés (2007). The red spectrum of wind noise is discussed by Raspet et al (2008) who note the strong roll-off towards higher frequencies.…”
Section: Spectral Analysis and Vent Velocitymentioning
confidence: 96%